Antibakteri Ekstrak Etanol 70% Herba Bandotan (Ageratum conyzoides Linn) Terhadap Bakteri Staphylococcus epidermidis - Nurbidayah Nurbidayah; Aditya Noviadi Rakhmatullah; Nanda Asysyifa Rivani (Universitas Borneo Lestari, 2024)
Bandotan herb (Ageratum conyzoides Linn) is a plant that has benefits in the health sector, one of which is used as an antibacterial. The ethanol extract of Bandotan Herb (Ageratum conyzoides Linn) has antibacterial properties against Staphylococcus aureus. This research aims to determine the phytochemical compounds in Bandotan Herb (Ageratum conyzoides Linn) and their antibacterial activity. The method used for antibacterial testing is well diffusion with 4 replications with concentrations of 10%, 20%, 40%, 60%, 80% and 100% and two controls, namely positive (Clindamycin 2µg) and negative (Na-CMC 0.5% ). Phytochemical screening is carried out using tube tests. The research results showed that the ethanol extract of Bandotan Herb (Ageratum conyzoides Linn) contains alkaloids, flavonoids, saponins, tannins, terpenoids and steroids. The diameter of the inhibition zone obtained was 3.14 mm, 4.26 mm and 5.77 in the weak category, in the medium category it was 7.44 mm and in the strong category it was 10.52 mm. Based on the results of the phytochemical test, it can be concluded that the ethanol extract of Bandotan Herb (Ageratum conyzoides Linn) is able to inhibit the growth of Staphylococcus epidermidis bacteria.